Genetic diversity and population structure of the boring giant clam (Tridacna crocea) in Kei Islands, Maluku, Indonesia (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Kusnadi A, Kurnianto D, Madduppa H, Zamani NP, Ibrahim PS, HernawanU E, Utami RT, Triandiza T. 2022. Genetic diversity and population structure of the boring giant clam (Tridacna crocea) in Kei Islands, Maluku, Indonesia. Biodiversitas 23: 1273-1282. Giant clams (Tridacninae) are ecologically important species in the coral reef ecosystems. They provide valuable functionsto traditional fisheries in Kei Islands, Maluku. However, their population isunder great pressure due to anthropogenic threats, such as overfishing and habitat degradation. To provide important data for devising effective conservation management strategies for giant clams, we investigated genetic diversity and population structure of the boring giant clams Tridacna croceain Kei Islands based on partial mitochondrial COI gene sequence. Tissue samples were collected from six sites: Kur, Dullah Laut, Tanimbar Kei, Dar, Labetawi, and Difur. We sequenced 477 base pairs of COI gene and identified 42 haplotypes and 52 polymorphic sites. Analysis of genetic diversity showed Dullah Laut and Dar had the highest genetic diversity. Population structure and genetic distance analysis showed unstructured populations with high genetic closeness among sites. This finding was also confirmed by the mixture pattern of the haplotype network. Further analysis using Bayesian models on gene flow revealed high genetic exchange among sites and that Dullah Population predominantly served as a source site for the other sites. This indicated a high probability of successful larval dispersal among sites. Based on these findings, we predict that the boring giant clams likely form a single population in Kei Islands. Our study warrants conservation priority for Dullah population as the main source of gene flow.